Influence of Collisions with Hydrogen Atoms on Non-LTE Effects for K I and Ca II in Stellar Atmospheres - Neretina, M. D.; Mashonkina, L. I.; Sitnova, T. M.; Yakovleva, S. A.; Belyaev, A. K. (Astronomy letters, 2020)
We have constructed a new K I model atom using currently available atomic data. We have performed calculations for K I by abandoning the assumption of local thermodynamic equilibrium (non-LTE) for the Sun and three moderately metal-poor dwarf stars. To take into account the inelastic processes in collisions with hydrogen atoms, for the first time we have used the rate constants calculated by including the fine structure of K I levels and analyzed the influence of their application on the non-LTE results compared to the use of the rate constants calculated for combined levels. In agreement with the non-LTE studies available in the literature, K I is subject to overrecombination, which leads to a strengthening of spectral lines and negative abundance corrections. The non-LTE effects are shown to weaken when using new collisional data. We reached the same conclusion when comparing the non-LTE corrections calculated for the Ca II 8662 Å line in model atmospheres with using the Ca II H I collision rates derived with and without allowance for the fine structure of Ca II levels. However, the effect is very small for the other two triplet lines, Ca II 8498 and 8542 Å. The solar non-LTE abundance derived from five lines is consistent with the meteoritic one within 0.01 dex. Despite the fact that in the atmospheres of the program stars the departures from LTE are larger than those in the Sun, the differential abundance [K/H] is almost independent of which collisional data set is used: the one calculated with or without allowance for the fine structure of K I levels.